STUDY OF MULTI-WALLED CARBON NANOTUBE/NICKEL/SILVER FOR THE DETECTION OF URIC ACID ASSOCIATED WITH CONTENT IN SWEAT ON SCREEN- PRINTED CARBON ELECTRODE (SPCE) AND FABRIC BASED SENSORS - Uperianti
In the development of biosensors, sensors are needed that are able to provide a fast response, have good sensitivity and selectivity, and are non-invasive. Among the various biosensor developments, electrochemical-based sensors receive special attention because they are non-invasive and easy to use. One type of sensor that has been widely developed is the screen-printed carbon electrode (SPCE). Recently, a wearable-based electrochemical biosensor with sweat as the detection sample has been developed. Sweat is rich in biomarkers such as electrolytes and metabolites that can be used to determine the condition of the body. To improve sensor performance, nanomaterials have been introduced to the biosensor field. Nanomaterial-based biosensors are one of the main topics in the diagnostic field because they can improve performance in terms of sensitivity In this study, SPCE sensors and fabric-based wearable sensors were developed to investigate uric acid levels associated with sweat content. Multi-walled carbon nanotube/Nickel/Silver nanomaterial (f-MWCNT/AgNi) is used as a recognition element in detecting uric acid. The characteristics of f-MWCNT/AgNi were